Identifying the Phenotypic and Temporal Heterogeneity of Knee Osteoarthritis: Data From the Osteoarthritis Initiative - Li, Mengjiao; Lan, Lan; Luo, Jiawei; Peng, Li; Li, Xiaolong; Zhou, Xiaobo (Frontiers in Public Health, 2021)
Objective: Previous studies discussing phenotypic and temporal heterogeneity of knee osteoarthritis (KOA) separately have fatal limitations that either clustering patients with similar severity or assuming all knees have a single common progression pattern, which are unreliable. This study tried to uncover more reliable information on phenotypic and temporal heterogeneity of KOA. Design: Data were from Osteoarthritis Initiative database. Six hundred and seventy-eight unilateral knees that have greater Kellgren and Lawrence (KL) grade than the contralateral knees at baseline and in all follow-up 48 months were included. Measurements of biomarkers at baseline were chosen. Subtype and Stage Inference model (SuStaIn) was applied as a subtype-progression model to identify subtypes, subtype biomarker progress sequences and stages of KOA. Results: This study identified three subtypes which account for 15, 61, and 24% of knees, respectively. Each subtype has distinct subtype biomarker progress sequence. For knees with KL grade 0/1, 2, 3, and 4, they have different distributions on stage and 26, 53, 89, and 95% of them are strongly assigned to subtypes. When assessing whether a knee has KL (grade ≥ 2), subtypes and stages from subtypes-progression model (SuStaIn) are significantly better fitting than those from subtypes-only (mixture of Gaussians) (likelihood ratio = 105.59, p = 2.2 × 10−16) or stages-only (SuStaIn where setting c = 1) (likelihood ratio = 58.04, p = 2.57 × 10−14) model. Stages in subtypes-progression model has greater β than stages-only model. Subtypes from subtypes-progression model have no statistical significance. Conclusions: For subtypes-progression model, stages contain more complete temporal information and subtypes are closer to real OA subtypes.